Similarity-Based Pattern Recognition Second International Workshop, SIMBAD 2013, York, UK, July 3-5, 2013, Proceedings - Hancock, Edwin; Pelillo, Marcello (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2013)
This book constitutes the proceedings of the Second International Workshop on Similarity Based Pattern Analysis and Recognition, SIMBAD 2013, which was held in York, UK, in July 2013. The 18 papers presented were carefully reviewed and selected from 33 submissions. They cover a wide range of problems and perspectives, from supervised to unsupervised learning, from generative to discriminative models, from theoretical issues to real-world practical applications, and offer a timely picture of the state of the art in the field.